FRAUD- BETWEEN DELINQUENCY AND CREATIVE ACCOUNTING - Violeta Isai; Daniela Hij (Risk in Contemporary Economy, 2015)
Nowadays, society continually changes, great technological transformations taking place and priorities changing without cease. Setting up new companies and quickly taking them into bankruptcy represents an actual tendency. Consequently, the contemporary economic environment becomes extremely competitive. Thus, economic operators have to face some choices which are not exactly within the law, in order to obtain additional advantages compared to the others, but also to keep their business going. The phenomenon of fraud is frequently encountered and it is present in any field of activity.